The Implementation of Learning Model React (Relating, Experiencing, Applying, cooperating And Transfering) Improving The Motivation and Learning Results Computer Skills and Information Management (KKPI) of Class XP1 Students subject of SMK Negeri 2 Singaraja In the Academic Year 2011/2012 - Putu Ayu Karunia Komala Dewi (Universitas Pendidikan Ganesha, 2012)
The classroom action research was aimed: (1) improving the students'motivation of class XP1 on microsoft excel material through the implementationof learning model REACT, (2) improving the students’ learning results of classXP1 in microsoft excel material through the implementation of learning modelREACT, (3) describing students’ response towards the implementation of learningmodel REACT in microsoft excel material.The current research was a CAR in which the subjects of the study werethe class XP1 students of SMK Negeri 2 Singaraja at the academic year2011/2012 with the object of the study being the students’ motivation to learn andtheir learning results on microsoft excel material. Data on students’ motivationwere collected using motivation questionnaires; cognitive test, psychomotoricobservation sheets, and affective observation sheets were utilized to gather data onstudents’ learning results; to collect data on students’ response, responsequestionnaire was employed. Data analysis of motivation, learning results andstudents’ response is done by determining the average score obtained, namelydividing the total score by the number of students.Based on the results of the revealed survey that: (1) the increase average ofstudents' motivation on subjects KKPI (Computer Skills and InformationManagement), especially on Microsoft Excel material was 7.49 or 11.48%, inwhich the average of student’s motivation in cycle I was 65.24 and in cycle II was72.73 high qualification, (2) the increase average of student’s learning outcomeswas 12.11 or 16.57% in which the average of student’s learning outcomes ofstudents 73.05 with classical completeness in cycle I was 59.46%, whereas incycle II was 85.16 with classical completeness was 91.89%, (3) student responsetoward the application of learning models REACT on subjects KKPI especially inMicrosoft Excel material was positive with average 78.22.